Proteomic Analysis Reveals the Protective Effects of Yiqi Fumai Lyophilized Injection on Chronic Heart Failure by Improving Myocardial Energy Metabolism - Han, Xiaoying; Zhang, Yi; Qiao, Ou; Ji, Haixia; Zhang, Xinyu; Wang, Wenzhe; Li, Xia; Wang, Juan; Li, Dekun; Ju, Aichun; Liu, Changxiao; Gao, Wenyuan (Frontiers in Pharmacology, 2021)
Yiqi Fumai lyophilized injection (YQFM) is the recombination of Sheng mai san (SMS).YQFM has been applied clinically to efficaciously and safely treat chronic heart failure (CHF). However, the mechanism of YQFM is still not fully elucidated. The purpose of our study was to investigate the protective mechanism of YQFM against abdominal aortic coarctation (AAC) in rats by proteomic methods.After YQFM treatment, the cardiac function were obviously meliorated. 157 important differentially expressed proteins (DEPs) were identified, including 109 in model rat compared with that in control rat (M:C) and 48 in YQFM-treated rat compared with that in model rat (T:M) by iTRAQ technology to analyze the proteomic characteristics of heart tissue. Bioinformatics analysis showed that DEPs was mainly involved in the body's energy metabolism and was closely related to oxidative phosphorylation. YQFM had also displayed efficient mitochondrial dysfunction alleviation properties in hydrogen peroxide (H2O2)-induced cardiomyocyte damage by Transmission Electron Microscope (TEM), Metabolic assay, and Mitotracker staining. What's more, the levels of total cardiomyocyte apoptosis were markedly reduced following YQFM treatment. Furthermore, Western blot analysis showed that the expressions of peroxisome proliferator activated receptor co-activator-1α(PGC-1α)(P < 0.01 or P < 0.001), perixisome proliferation-activated receptor alpha (PPAR-α) (P < 0.001)and retinoid X receptor alpha (RXR-α) were upregulated (P < 0.001), PGC-1α as well as its downstream effectors were also found to be upregulated in cardiomyocytes after YQFM treatment(P < 0.001).These results provided evidence that YQFM could enhance mitochondrial function of cardiomyocytes to play a role in the treatment of CHF by regulating mitochondrial biogenesis-related proteins.